Gilbert Syndrome and Blood Diseases - OHTA, Shigeru; MARUO, Yoshihiro (The Japanese Journal of Pediatric Hematology, 2004)
Gilbert syndrome is a mild type of hereditary unconjugated hyperbilirubinemias, caused by the mutations of the bilirubin UDP-glucuronosyltransferase gene (UGT1A1). Incidence of a severe and moderate form of hereditary unconjugated hyperbilirubinemias, Crigler-Najjar syndrome, is rare. However, Gilbert syndrome is the most frequent metabolic disease and incidence of Gilbert syndrome is 3-7% of the population. Thus 3-7% of patients with blood disease have Gilbert syndrome simultaneously. In the Japanese population, there are two major polymorphisms of UGTIAI which cause Gilbert syndrome : G71R in exon 1 and A (TA) 7TAA of TATA box in the promoter region. Allele frequencies of those polymorphisms are 0.16 and 0.15, respectively. Not only patients with Gilbert syndrome caused by homozygous or compound heterozygous mutations [G71R and A (TA) 7TAA], but also heterozygous carriers of the mutations contribute to modification of the situation of blood diseases. Recently reports were published on the association of Gilbert syndrome and blood disease. Co-occurrence of hereditary spherocytosis and Gilbert syndrome increases the risk of gallstones. When leukemia patients with UGT1A1 mutations receive chemotherapy, transiently unconjugated hyperbilirubinemia develops. This review provides an overview of bilirubin UDP-glucuronosyltransferase and the association between Gilbert syndrome and blood diseases.